Security dynamics of East Asia in the Gulf region - Niblock, Tim; Guang, Yang (Gerlach Press, 2014)
The Gulf region's primary economic relationships are rapidly shifting from West to East. Relations with China, Japan and South Korea are becoming increasingly strategic in nature: based on a degree of mutual dependence far greater than is present in Gulf-Western relations. The balance of global politics will be critically affected by this powerful emerging relationship. This book provides documentation of the trend and examines some of the political and strategic issues which follow from it.